T-Cell Immunity to Influenza in Older Adults: A Pathophysiological Framework for Development of More Effective Vaccines - McElhaney, Janet E.; Kuchel, George A.; Zhou, Xin; Swain, Susan L.; Haynes, Laura (Frontiers in Immunology, 2016)
One of the most profound public health consequences of immune senescence is reflected in an increased susceptibility to influenza and other acute respiratory illnesses, as well as a loss of influenza vaccine effectiveness in older people. Common medical conditions and mental and psychosocial health issues as well as degree of frailty and functional dependence accelerate changes associated with immune senescence. All contribute to the increased risk for complications of influenza infection including pneumonias, heart diseases and strokes that lead to hospitalization, disability and death in the over 65 population. Changes in mucosal barrier mechanisms and both innate and adaptive immune functions converge in the reduced response to influenza infection, and lead to a loss of antibody-mediated protection against influenza with age. The interactions of immune senescence and reduced adaptive immune responses, persistent cytomegalovirus infection, inflammaging (chronic elevation of inflammatory cytokines), and dysregulated cytokine production, pose major challenges to the development of vaccines designed to improve T-cell mediated immunity. In older adults, the goal of vaccination is more realistically targeted to providing clinical protection against disease rather than to inducing sterilizing immunity to infection. Standard assays of antibody titres correlate with protection against influenza illness but do not detect important changes in cellular immune mechanisms that correlate with vaccine-mediated protection against influenza in older people. This article will discuss: i) the burden of influenza in older adults and how this relates to changes in T cell function, ii) age-related changes in different T cell subsets and immunologic targets for improved influenza vaccine efficacy in older, and iii) the development of correlates of clinical protection against influenza disease to expedite the process of new vaccine development for the 65 and older population. Ultimately, these efforts will address the public health need for improved protection against influenza in older adults and “vaccine preventable disability”.